Matlab simulation of lithium ion cell using electrochemical single particle model - Tran, N.; Vilathgamuwa, M.; Farrell, T.; Choi, San Shing (2016)
© 2016 IEEE. Battery modelling is a significant component of advanced Battery Management Systems (BMSs). The full electrochemical model of a battery can represent high precision battery behavior during its operation. However, the high computational requirement to solve the coupled nonlinear partial differential equations (PDEs) that define these models limits their applicability in an online BMS, especially for a battery pack containing hundreds of cells. Therefore, a reduced SPM-Three parameter model is proposed in this paper to efficiently model a lithium ion cell with high accuracy in a specific range of cell operation. The reduced model is implemented in a Simulink block for developing an advanced battery modelling tool that can be applied to a wide variety of battery applications.